1997
DOI: 10.1101/gad.11.11.1464
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin E-CDK2 is a regulator of p27Kip1.

Abstract: CDK inhibitors are thought to prevent cell proliferation by negatively regulating cyclin-CDK complexes. We propose that the opposite is also true, that cyclin-CDK complexes in mammmalian cells can promote cell cycle progression by directly down-regulating CDK inhibitors. We show that expression of cyclin E-CDK2 in murine fibroblasts causes phosphorylation of the CDK inhibitor p27 Kip1 on T187, and that cyclin E-CDK2 can directly phosphorylate p27 T187 in vitro. We further show that cyclin E-CDK2-dependent phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

46
718
2
5

Year Published

1998
1998
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 852 publications
(771 citation statements)
references
References 51 publications
(59 reference statements)
46
718
2
5
Order By: Relevance
“…Northern blot analysis of the p27 Kip1 transcripts revealed no signi®cant di erences in all cell lines regardless of their IL-2 status (Figure 1b and c). Thus, the maintenance of a low steady state level of p27 Kip1 in HTLV-I-transformed (IL-2 independent) cells appears to be regulated at a post-transcriptional level, consistent with the notion that p27 Kip1 cellular level is regulated by phosphorylation and ubiquitination (Pagano et al, 1995;Shea et al, 1997;Vlach et al, 1997).…”
Section: P27 Kip1 Expression In Htlv-i-infected T-cell Linessupporting
confidence: 78%
“…Northern blot analysis of the p27 Kip1 transcripts revealed no signi®cant di erences in all cell lines regardless of their IL-2 status (Figure 1b and c). Thus, the maintenance of a low steady state level of p27 Kip1 in HTLV-I-transformed (IL-2 independent) cells appears to be regulated at a post-transcriptional level, consistent with the notion that p27 Kip1 cellular level is regulated by phosphorylation and ubiquitination (Pagano et al, 1995;Shea et al, 1997;Vlach et al, 1997).…”
Section: P27 Kip1 Expression In Htlv-i-infected T-cell Linessupporting
confidence: 78%
“…Both proteins are regulated at a post-transcriptional level. Among the kinases that regulate p27 degradation is cdk2 itself (Sheaff et al, 1997). Phosphorylation of p27 by cdk2 induces ubiquitylation of the protein, and this may partially account for the reduced p27 protein levels in junB D/D cells that indeed show elevated cdk2 kinase activity.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, this hypothesis is consistent with the results of U È ren et al (1997) which have shown that N-terminal and C-terminal domains of p27 can be endowed of opposite e ects. Recent works (Morisaki et al, 1997;Shea et al, 1997;Vlach et al, 1997) have demonstrated that the phosphorylation of the Threonine 187 by cyclin E/CDK2 triggers the degradation of p27 following the ubiquitin/proteasome pathway. Mutagenesis experiments have shown that the mutation of this residue into Alanine or Valine prevents p27 degradation.…”
Section: Discussionmentioning
confidence: 99%